2013
DOI: 10.4314/ahs.v13i2.14
|View full text |Cite
|
Sign up to set email alerts
|

Malaria and HIV co-infection and their effect on haemoglobin levels from three healthcare institutions in Lagos, southwest Nigeria

Abstract: Background: Malaria and human immunodeficiency virus (HIV) are two major infections with enormous public health consequence. Together, they are endemic in many developing countries with anaemia being the most frequent haematological consequence of the infections. Objective: To determine the prevalence of malaria and HIV co-infection as well as anaemia among selected patients from three health-care institutions in Lagos, Nigeria. Methods: A cross-sectional study of 1080 patients was carried out to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
3
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 30 publications
3
51
3
3
Order By: Relevance
“…It has been reported that impaired haematopoiesis, immune-mediated cytopenias, and altered coagulation mechanisms do occur in HIV-infected individuals, probably as a result of HIV infection itself, as sequelae of HIV-related opportunistic infections or malignancies, or as a consequence of treatments used for HIV infection and related condition. This report is similar to that of a study carried out in Lagos Nigeria [30] where patients co-infected with malaria and HIV were more likely to be anaemic.…”
Section: Discussionsupporting
confidence: 79%
“…It has been reported that impaired haematopoiesis, immune-mediated cytopenias, and altered coagulation mechanisms do occur in HIV-infected individuals, probably as a result of HIV infection itself, as sequelae of HIV-related opportunistic infections or malignancies, or as a consequence of treatments used for HIV infection and related condition. This report is similar to that of a study carried out in Lagos Nigeria [30] where patients co-infected with malaria and HIV were more likely to be anaemic.…”
Section: Discussionsupporting
confidence: 79%
“…Anemia, increase plasma viral load and decrease CD4 count among HIV infected are some of the worse health outcomes due to frequent episodes of symptomatic malaria [2] [3][4]. HIV may facilitates geographic expansion of malaria in areas where HIV prevalence is high.…”
Section: Introductionmentioning
confidence: 99%
“…Malaria, a mosquito-borne parasitic infection caused by species of Plasmodium, is the leading cause of pregnancyassociated death in sub-Saharan Africa (Sanyaolu et al, 2013;Sonny-Johnbull et al, 2014;Gething et al, 2016;Maitland, 2016;Sued et al, 2016). In sub-Saharan Africa, 25 million pregnant women are currently at risk for malaria, accounting for 10,000 maternal and 200,000 neonatal deaths per year (Matangila et al, 2014;Mbah et al, 2015).…”
Section: Introductionmentioning
confidence: 99%